25-هيدروكسي فيتامين د3 لدى مرضى الداء القلبي الإقفاري المشخصين حديثاً: دراسة ميدانية - رضوان, فيصل; معروف, باسم; عمران, شغف (Latakia University Journal -Medical Sciences Series, 2018)
Cardiovascular disease is the leading cause of morbidity and mortality in the world and is one of the most common diseases worldwide. Considering that comes vitamin D as an anti-atherogenic potential factor, supported by a lot of studies that describe his relationship with cardiovascular disease, and this study aims to compare serum levels of vitamin D among cardiovascular disease patients and healthy people within the Syrian coast area. Study sample was divided into two groups; Patients group: included 50 patients who admitted for coronary angiography at Tishreen University hospital in Lattakia, patients had ≥50% stenosis at least in one major coronary artery, control group: included 42 patients had normal coronary arteries and no angiographic evidence of artery occlusion. The serum levels of vitamin D among the two groups of the study have been measured by the enzyme-linked immunosorbent assay technique (ELISA). The results showed a clear decline in vitamin D values in patients group compared with the control group, where the average values 12.1ng/ml versus 17.4 ng/ml (P-V=0.000). In addition, we found that the decreased levels of serum vitamin D corresponded with smoking, having fish less than one time a week. we hadn’t find a relationship links serum levels of vitamin D with the number of stenotic major coronary arteries (one vessel-double vessel-triple vessel) (P-V=0.463) or with the severity of stenosis (graded as 50%-70%, >70%-90% - >90%) in the patients group (P-V=0.404). In conclusion, necessity of measuring the serum level of vitamin D in ischemic heart disease patients especially newly diagnosed, that may help in more maximal management to the patient. يعد الداء القلبي الإكليلي السبب الرئيسي المؤدي للوفاة والعجز في العالم، وهو أحد أكثر الأمراض شيوعاً في العصر الحديث، ضمن هذا الواقع يأتي الفيتامين د كعامل مضاد محتمل، مدعم ذلك بمئات الدراسات التي تصف علاقته مع أمراض الأوعية الإكليلية. تهدف هذه الدراسة إلى مقارنة المستويات المصلية لفيتامين د بين الأشخاص الأصحاء والأشخاص المصابين بالداء القلبي الإكليلي في منطقة الساحل السوري. تم تقسيم عينة البحث إلى مجموعتين؛ مجموعة المرضى: شملت 50 مريض من الذين خضعوا لتصوير الأوعية الإكليلية الظليل في مشفى تشرين الجامعي في مدينة اللاذقية، والذي أظهر تصوير الأوعية الإكليلية لديهم تضيق ≥50% في شريان إكليلي رئيسي واحد على الأقل من الشرايين الإكليلية الرئيسية، مجموعة الشاهد: شملت 42 مريضاً من الذين أظهر تصوير الأوعية لديهم أن الشرايين الإكليلية سليمة ولا يوجد فيها أي لويحة عصيدية، وقمنا بدراسة المستويات المصلية لفيتامين د لدى مجموعتي الدراسة بطريقة المقايسة المناعية الإنزيمية(ELISA). أظهرت النتائج انخفاضاً واضحاً في قيم فيتامين د لدى مجموعة المرضى بالمقارنة مع مجموعة الشاهد حيث كان متوسط القيم12.1 ng/ml مقابل 17.4 ng/ml (P-V= 0.000)، كما وجدنا أن القيم الأخفض لفيتامين د كانت بنسبة أعلى لدى المرضى المدخنين وعند الأشخاص الذين يتناولون السمك بمعدل أقل من مرة/أسبوعياً، ولم نجد علاقة تربط المستويات المصلية لفيتامين د مع عدد الشرايين الإكليلية المتضيقة (شريان واحد، شريانين اثنين، ثلاث شرايين) (P-V= 0.463) أو مع درجة التضيق الوعائي لدى مجموعة المرضى (70-50%،%90-70<،>90%) (P-V=0.404)، بالنتيجة ضرورة إجراء معايرة فيتامين د لجميع مرضى الداء القلبي الإقفاري خاصةً المشخصين حديثاً، مما قد يخدم في تدبير أكثر شمولية للمريض.